Antibiotic Alternatives in Poultry and Fish Feed 2022
DOI: 10.2174/9789815049015122010008
|View full text |Cite
|
Sign up to set email alerts
|

Clove (Syzygium aromaticum) and its Derivatives in Poultry Feed

Abstract: Production of safe and healthy poultry diets of high profitability is the central aim of poultry men. This safety is achieved by using natural products as growth stimulants. Natural feed additives such as medicinal products derived from herbs and spices are mainly used in the poultry feed industry as appetite and enzyme secretion stimulants. The use of clove (Syzygium aromaticum) and its derivatives has lately received much greater attention as an alternative to traditional antibiotics. The clove exhibited str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To reduce the effect of cell wall's hiding nutrients, effective combinations of NSP-degrading enzymes could be used, enhancing starch, protein, and energy consumption. Preparations of multienzyme in feed increase fiber digestibility in feed components by targeting several substrates (Alagawany et al, 2018).).…”
Section: Exogenous Enzymes In Poultry Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the effect of cell wall's hiding nutrients, effective combinations of NSP-degrading enzymes could be used, enhancing starch, protein, and energy consumption. Preparations of multienzyme in feed increase fiber digestibility in feed components by targeting several substrates (Alagawany et al, 2018).).…”
Section: Exogenous Enzymes In Poultry Dietsmentioning
confidence: 99%
“…The addition of enzymes in rations improved nutrient digestibility, resulting in increased efficiency and performance. Furthermore, adding commercial enzymes to feed ingredients and diets boosted the nutritive value while allowing for more variety in diet formulation (Alagawany et al, 2018). Exogenous multi-enzyme supplementation (xylanases, ßglucanases, pectinases, celluloses, and arabinofuranosidases) improved the nutritional value of the maize-soy diet by 3%, as it could pay costs for the 3% reduction in nutrients such as energy, protein, calcium, and phosphorus) through improved FCR (Kutlu et al, 2019).…”
Section: Nutrient Digestibilitymentioning
confidence: 99%
“…Exogenous enzymes were used either to compensate for the lack of enzymes in bird or assist in digestion of some diet materials high with fiber to improve growth rate by increasing rate of digestion of carbohydrates, proteins and oil and thus increasing represented energy or to assist in the decomposition of some anti-nutritional materials in the components of the feed [15]. Studies have revealed that effectively addressing poultry feeding problems by increasing the protein utilization, oil and carbohydrates and increasing the ability to absorb calcium and some trace elements through the use of enzymes [17]. It is known that poultry does not have enough internal enzymes for digestion most of the nutrients, thus adding enzymes to poultry feed helps to improve the digestive value.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to that, other investigators claim no in uence of enzyme blends containing xylanase, cellulase, and phytase(Sayehban et al, 2016) in this regard. The increase in the BW and WG as a result of multi-enzyme supplementation could be attributed to the role of these exogenous enzymes in breaking down the NSP and thus reducing the bre content of the diet(Alagawany et al, 2018), overcoming the antinutritional components, improving feed consumption, and enhancing performance(Jia et al, 2009;Attia et al, 2012) Choct et al (1995).…”
mentioning
confidence: 99%